Correction of "Wrist" Deformity in Radial Dysplasia: A Systematic Review and Meta-Analysis. (20th December 2017) - Murphy, George R.F.; Logan, Malcolm P.O.; Smith, Gill; Sivakumar, Branavan; Smith, Paul
Abstract : Background: Radial dysplasia affects 1 in 6, 000 to 8, 000 births, classically presenting with a shortened, bowed ulna and radially deviated hand. The optimal treatment remains unclear, with several opposing approaches advocated. This review aims to clarify the long-term outcomes of nonsurgical and surgical treatment of the "wrist" deformity. Methods: The Embase, MEDLINE, PubMed, Cochrane Central, ClinicalTrials.gov, and World Health Organization International Clinical Trials Registry Platform (ICTRP) databases were searched for published and unpublished studies reporting long-term outcomes of surgical or nonsurgical treatment of children with radial dysplasia. Results were not restricted by date or language. Primary outcomes were hand-forearm angle, ulnar length, and "wrist" active range of motion (ROM). Studies were assessed using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) criteria. Data for the change in hand-forearm angle were pooled using random-effects meta-analysis, and mean differences and 95% confidence intervals were obtained. Primary outcome data at last follow-up were pooled, and means and standard deviations were obtained. The PROSPERO registration of this study was CRD42016036665. Results: Of 104 studies identified, 12 were included in this review. Five were retrospective cohort studies and 7 were case series. No randomized studies were found. Study quality was low or very low according to the GRADE criteria. The hand-forearm angle of nonsurgically treated patients worsened during childhood, from 66° to 84°, whereas "wrist" active ROM, at 61°, was better than that for most surgically treated patients. Ulnar length with nonsurgical treatment was predicted to be 64% of normal, but was not directly reported. Isolated soft-tissue release provided a modest reduction in hand-forearm angle compared with nonsurgical treatment. Soft-tissue distraction with centralization or radialization achieved the best hand-forearm angle correction (16° radial deviation). Radialization maintained better "wrist" active ROM (46°) and ulnar length than centralization. Microvascular second metatarsophalangeal joint transfer yielded better reported "wrist" active ROM (83°) and good ulnar length compared with other surgical techniques, but a slightly worse hand-forearm angle (28°). Conclusions: There was low-quality evidence that soft-tissue distraction plus centralization or radialization achieved the best correction of the hand-forearm angle for children with radial dysplasia. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.